2006
DOI: 10.4315/0362-028x-69.8.1997
|View full text |Cite
|
Sign up to set email alerts
|

Fates of Seeded Escherichia coli O157:H7 and Salmonella on Selected Fresh Culinary Herbs during Refrigerated Storage

Abstract: The fates of seeded Escherichia coli O157:H7 and Salmonella on selected fresh culinary herbs were evaluated at a refrigerated temperature (4 degrees C). Fresh herbs, including cilantro, oregano, basil, chive, parsley, and rosemary, were inoculated with six-strain mixtures of E. coli O157:H7 and Salmonella, and the microbial populations were monitored at 1, 5, 11, 16, 19, and 24 days. For both pathogens, a significant decrease in the population (P < 0.0001) occurred within the first 5 days of storage (< 0.8 log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 19 publications
1
16
0
2
Order By: Relevance
“…These findings lend support to recent studies that looked at herb contamination by Salmonella (14) and E. coli 0157 (16). Similarly, Hsu et al (13) found that E. coli 0157:H7 and Salmonella survived on fresh herbs, including basil. The phyllosphere of plants is a harsh environment for enteric pathogenic bacteria, and it is expected that there will be a reduction in numbers (15).…”
Section: Discussionmentioning
confidence: 89%
“…These findings lend support to recent studies that looked at herb contamination by Salmonella (14) and E. coli 0157 (16). Similarly, Hsu et al (13) found that E. coli 0157:H7 and Salmonella survived on fresh herbs, including basil. The phyllosphere of plants is a harsh environment for enteric pathogenic bacteria, and it is expected that there will be a reduction in numbers (15).…”
Section: Discussionmentioning
confidence: 89%
“…and/or L. monocytogenes has been studied in several vegetables such as broad leafy endives (Carlin et al, 1995), lettuces (Koseki and Isobe, 2005a,b), carrots (Finn and Upton, 1997), cabbage (Finn and Upton, 1997), peppers and tomatoes , herbs (Hsu et al, 2006), spinach (Pirovani et al, 2000), and radish (Islam et al, 2004) but not in RTE collard greens, watercress, arugula and mix for yakisoba. Therefore, the current study reports for the first time the growth potential of Salmonella and L. monocytogenes in these RTE vegetables.…”
Section: Resultsmentioning
confidence: 99%
“…Foodborne outbreaks occurred with strawberries and basil after transport and storage, suggesting survival of E. coli 0157:H7 or Salmonella on both commodities, even in adverse environ ments. Although survival of these pathogens has been studied on leafy greens, such as spinach (45,54), escarole (1,54), and especially, on fresh-cut iceberg or romaine lettuce (11,20,22,58,61), and growth models are available for iceberg lettuce (37,47) to predict growth of E. coli under temperature abuse, limited information is available about the survival of E. coli 0157:H7 and Salmonella on basil leaves during storage (29,35). Moreover, no information about the survival of Salmonella or E. coli 0157:H7 on basil leaves during storage at 15°C is available, which is the recom mended temperature to maintain quality during storage.…”
mentioning
confidence: 99%